Citizenship Education in Elementary Schools (Foundations for Personality Development of Future Citizens) - Rahmadani Gultom (International Journal of Students Education, 2024)
This research aims to evaluate the effectiveness of citizenship education (PKN) in elementary schools in instilling basic civic values, developing social skills and empathy in students. This research was conducted through a literature study method, where data and information were collected systematically from various written sources. scientific which includes academic journals, textbooks, conference articles, and relevant government documents. This research reveals that the use of interactive teaching methods by teachers has succeeded in increasing students’ understanding of their rights and obligations as citizens, as well as increasing their social skills and empathy. However, the research results also show that there are several significant challenges, such as limited resources and inconsistencies in the understanding and application of PKN material by teachers. This variability results in differences in the quality of citizenship education received by students in different schools. This study recommends the development of more comprehensive teacher training strategies and the provision of adequate resources to support effective PKN teaching. It is hoped that greater investment in Civics education will strengthen the consistency and quality of the program, ensuring that all students gain similar and in-depth civics skills and knowledge.